Non-asset digital platforms for the personal care industry in South Africa - Van den Berg, Anton (My University, 2020)
This research project was conducted to examine if the South African personal care industry will adopt a non-asset based digital platform business model on creating more economic opportunities for graduate students within the personal care industry in South Africa. The research was done through two sets of data collection through quantitative survey questionnaires. The one set at understanding the supply-side characteristics necessary for a successful non-asset based digital platform within the personal care industry in South Africa and if the proposed platform business model could be successfully adopted by the supply-side, meaning personal care service providers who deliver services such as beauty, nail treatments, make-up treatments etc. The second quantitative questionnaire was to understand the characteristics the consumers of personal care services within South Africa would value to adopt the proposed new business model. Both sets of research revealed that the market is favourable for the adoption of the proposed new business model and will adopt it if it creates more economic benefit for both sides of the platform as well as convenience. To conclude, the research and frameworks used throughout this research project have highlighted critical characteristics from a platform design as well as the necessary facilitating conditions and characteristics needed for a successful implementation of the proposed transformative business model.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Exponential organisations; Multisided platform; Personal care services; Sharing economy; Transformative business model; Big data; SDG-8: Decent work and economic growth